Cell‐derived and enzyme‐based decellularized extracellular matrix exhibit compositional and structural differences that are relevant for its use as a biomaterial. Issue 4 (9th February 2022) - Nellinger, Svenja; Mrsic, Ivana; Keller, Silke; Heine, Simon; Southan, Alexander; Bach, Monika; Volz, Ann‐Cathrin; Chassé, Thomas; Kluger, Petra J.
Abstract: Due to its availability and minimal invasive harvesting human adipose tissue‐derived extracellular matrix (dECM) is often used as a biomaterial in various tissue engineering and healthcare applications. Next to dECM, cell‐derived ECM (cdECM) can be generated by and isolated from in vitro cultured cells. So far both types of ECM were investigated extensively toward their application as (bio)material in tissue engineering and healthcare. However, a systematic characterization and comparison of soft tissue dECM and cdECM is still missing. In this study, we characterized dECM from human adipose tissue, as well as cdECM from human adipose‐derived stem cells, toward their molecular composition, structural characteristics, and biological purity. The dECM was found to exhibit higher levels of collagens and lower levels of sulfated glycosaminoglycans compared with cdECMs. Structural characteristics revealed an immature state of the fibrous part of cdECM samples. By the identified differences, we aim to support researchers in the selection of a suitable ECM‐based biomaterial for their specific application and the interpretation of obtained results. Abstract : In this study native decellularized extracellular matrix (ECM) from adipose tissue and cell‐derived ECM from adipose‐derived stem cells (stem cell state and adipogenic differentiated) are systematically characterized and compared. Differences are shown in macromolecular composition, structural features and biological purity. These differences might be relevant for cellular behavior of reseeded cell and affect experimental outcome and should therefore be considered when choosing a biomaterial for a specific application or interpreting obtained results. (Created with BioRender.com ).